(untitled) (World Bulletin of Public Health, 2026)
In the Republic of Uzbekistan, the frequency of chronic recurrent aphthous stomatitis among all diseases of MOP is 6.22% and tends to increase, therefore, the study of the cytogenetic and cytotoxic parameters of buccal epithelium in patients is of undoubted practical interest [5]. The aim of the study was to study the cytogenetic and cytotoxic parameters of buccalepithelium in patients with chronic recurrent aphthous stomatitis. Recurrent aphthous stomatitis accounts for up to 90% of all violations of the integrity of the oral mucosa encountered in dental practice. Thus, a significant excess of cytogenetic and karyological disorders was established in patients with a scarring form of the disease in all periods of chronic recurrent aphthous stomatitis